Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-021-04321-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal genome-wide DNA methylation changes in response to kidney failure replacement therapy

Abstract: Chronic kidney disease (CKD) is an emerging public health priority associated with high mortality rates and demanding treatment regimens, including life-style changes, medications or even dialysis or renal transplantation. Unavoidably, the uremic milieu disturbs homeostatic processes such as DNA methylation and other vital gene regulatory mechanisms. Here, we aimed to investigate how dialysis or kidney transplantation modifies the epigenome-wide methylation signature over 12 months of treatment. We used the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…A most recent study compared epigenome-wide methylation modification between healthy patients and renal failure replacement therapy patient (dialysis and kidney transplantation) at baseline (right before renal failure replacement therapy) and over 12 months treatment, they found that uremic milieu drives genome-wide methylation changes but partially reversed with kidney failure replacement therapy. However, 413 CpG sites remained differentially methylated at follow-up in renal replacement therapy, which merit further investigation (40). These observations suggest a role of DNA methylation in chronic inflammation, IF/TA and chronic allograft dysfunction in kidney transplantation.…”
Section: Chronic Rejection and Interstitial Fibrosis/ Tubular Atrophymentioning
confidence: 86%
“…A most recent study compared epigenome-wide methylation modification between healthy patients and renal failure replacement therapy patient (dialysis and kidney transplantation) at baseline (right before renal failure replacement therapy) and over 12 months treatment, they found that uremic milieu drives genome-wide methylation changes but partially reversed with kidney failure replacement therapy. However, 413 CpG sites remained differentially methylated at follow-up in renal replacement therapy, which merit further investigation (40). These observations suggest a role of DNA methylation in chronic inflammation, IF/TA and chronic allograft dysfunction in kidney transplantation.…”
Section: Chronic Rejection and Interstitial Fibrosis/ Tubular Atrophymentioning
confidence: 86%
“…These authors also noted distinct localisation patterns for differentially methylated CpG sites for dialysis and transplant patients, and highlighted that the methylation status of regions associated with cellular aging or metabolism were particularly altered 12 months post-treatment, to become more in line with healthy control participants (139). 413 differentially methylated genes present in both dialysis and transplant patients remained unaltered 12 months post-treatment, identifying potentially distinct and robust CKD markers warranting future study (139).…”
Section: Epigenetic Modifications Provide An Additional Layer Of Vari...mentioning
confidence: 98%
“…Existing evidence suggests that DNA methylation plays a crucial role in the pathogenesis of kidney diseases (Chen et al, 2021; Witasp et al, 2022). Changes in DNA methylation can modify mitochondrial functions by either upregulating or suppressing the genes responsible for cellular processes such as an increase in ROS generation and alteration in energy metabolism (Lopes, 2020).…”
Section: Mitochondrial Dynamics In Kidney Diseasesmentioning
confidence: 99%